Struktur Iklan Dalam Bahasa Indonesia - Drs. Suharyo, M.Hum.; Fitri, S.S. (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2012)
Language usage in "kecik" ad in "Suara Merdeka" was almost overlook that it actually (read: "kecik" ad) is one of the literary phenomenon that is not less interesting than the other literary phenomenon. If during this time can be said to escape from the attention perhaps because it is a small "kecik" thing, but if further researched it is quite interesting. First, for example in terms of morphology it is found the structure of contraction, perpetuation of consonants and vowels, like "jl (jual or jalan), ist (istimewa), BU (butuh uang), cpt (cepat), PS (power steering)". Second, from the aspect of syntactic the structure of "kecik" ad is characterized by perpetuation of a form of the phrase, as well as the utilization of various forms of active and passive sentences, etc. Third, from the aspect of lexicon in "kecik" ad is turned out to be structured in Indonesian, English, Javanese, and Betawi language, for example, in the ad is found some Javanese words like "maknyus, anyar, cespleng"; in Indonesian with Betawi dialect like "doang"; and in English like "PS (power steering)".Key words: structure, ad, "kecik"